2018
DOI: 10.1242/bio.027730
|View full text |Cite
|
Sign up to set email alerts
|

Cell tracking in vitro reveals that the extracellular matrix glycoprotein Tenascin-C modulates cell cycle length and differentiation in neural stem/progenitor cells of the developing mouse spinal cord

Abstract: Generation of astrocytes during the development of the mammalian spinal cord is poorly understood. Previously, we have shown that the glycoprotein of the extracellular matrix (ECM) tenascin-C (Tnc) modulates the expression territories of the patterning genes Nkx6.1 and Nkx2.2 in the developing ventral spinal cord, tunes the responsiveness of neural stem/progenitor cells towards the cytokines FGF2 and EGF and thereby promotes astrocyte maturation. In order to obtain further mechanistic insight into these proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
(87 reference statements)
1
24
0
Order By: Relevance
“…At the same time, NSPCs isolated from the spinal cord of tenascin-C-deficient mice were analyzed in an analogous manner for an independent experimental approach. The dataset regarding the untreated control cells served as reference both for the chlorate-treated and the tenascin-C depleted NSPCs and has been published in the latter context ( May et al, 2018 ). Here, as the experiments have been conducted in parallel, this data set of the control cells was used as reference to evaluate the influence of inhibited sulfation on spinal cord-derived NSPCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, NSPCs isolated from the spinal cord of tenascin-C-deficient mice were analyzed in an analogous manner for an independent experimental approach. The dataset regarding the untreated control cells served as reference both for the chlorate-treated and the tenascin-C depleted NSPCs and has been published in the latter context ( May et al, 2018 ). Here, as the experiments have been conducted in parallel, this data set of the control cells was used as reference to evaluate the influence of inhibited sulfation on spinal cord-derived NSPCs.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, full lineage trees originating from an individual stem cell could be constructed in that manner. A previous study of the laboratory illustrates this procedure, documenting the simultaneous construction of lineage trees in parallel with the time-lapse video ( May et al, 2018 ). Movies were created using ImageJ 1.45r (National Institutes of Health) software and are played at a speed of five frames per second (see Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presently available tools for single-cell tracking are missing methodology to resolve ambiguities such as joint multi-target tracking and classification (Hilsenbeck et al, 2016;Hormoz et al, 2016;Rapoport et al, 2011;Stadler et al, 2018). However, the development of software tracking tools is under constant improvement (Davis et al, 2007;Errington et al, 2005;Khan et al, 2007;Koh et al, 2017;May et al, 2018). The latest advancements appear to focus on automation based on localized image analysis and recognition.…”
Section: Single Live-cell Tracking For Identification Of Drug-resistant and Aggressive Cancer Cellsmentioning
confidence: 99%
“… 19 , 20 For tenascin-C, it was shown that it modulates cell cycle length and differentiation in neural stem/progenitor cells and participates in the formation of the radial glia type B of the adult CNS stem cell niches. 21 , 22 However, it remains unclear how these proteins and their active peptides influence on drNPC differentiation.…”
Section: Introductionmentioning
confidence: 99%